2018
DOI: 10.2967/jnumed.118.218248
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolic Changes Related to Freezing of Gait in Parkinson Disease

Abstract: Freezing of gait (FOG) in Parkinson disease (PD) often occurs during steering of gait (i.e., complex gait), which is thought to arise from executive dysfunction. Our aim was to test whether cognitive corticobasal ganglia-thalamocortical circuitry is impaired and whether alternate neural circuits are used for complex gait in PD with FOG. Methods: Eighteen individuals with idiopathic PD in the off-medication state, 9 with FOG (aged 68 ± 6 y) and 9 without FOG (aged 65 ± 5 y), were included. PET was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In contrast, other studies showed hyper rather than hypometabolism in specific frontal areas (e.g. paracentral lobule) (Mitchell et al., 2019; Tard et al., 2015). Studies investigating subcortical brain regions with PET also described functional abnormalities in subcortical structures such as the basal ganglia (Bartels et al., 2006; Tard et al., 2015) and MLR (Tard et al., 2015.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast, other studies showed hyper rather than hypometabolism in specific frontal areas (e.g. paracentral lobule) (Mitchell et al., 2019; Tard et al., 2015). Studies investigating subcortical brain regions with PET also described functional abnormalities in subcortical structures such as the basal ganglia (Bartels et al., 2006; Tard et al., 2015) and MLR (Tard et al., 2015.…”
Section: Resultsmentioning
confidence: 65%
“…(2016)40 PD patients (69±8; 11 PD-nFOG) 11 HS (64±7)6- 18 [F]-FMTAADC activityReduced FMT uptake in putamen, caudate and LC in PD patients than HSSeverity of FOG negatively correlated with FMT uptake in LCGallardo et al. (2018)9 PD-FOG (NA) 8 PD-nFOG (NA) 18 [F]-FDGGlucose metabolismFrontal and predominantly right-sided hypometabolismNot performedMitchell et al. (2019)9 PD-FOG (68±6) 9 PD-nFOG (65±5) 18 [F]-FDGGlucose metabolism during steering of gait compared to straight walkingChanges in cortico-thalamic circuit and hyperdirect pathway (reduced activation of parietal regions; reduced deactivation of prefrontal regions and thalamus; increased activation of supplementary motor area) during staring of gaitActivity in right dorsolateral prefrontal cortex negatively correlated with stride length during steering of gaitBohnen et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study revealed that patients with “on” FoG had less activation of the posterior parietal cortex and less deactivation of the dorsolateral PFC and thalamus, and increase activation in the supplementary motor area (28). The supplementary motor area has direct projections to the STN responsible for strong inhibition of a planned action (29, 30) and is strongly activated during real FoG episodes (31).…”
Section: Discussionmentioning
confidence: 99%